Examining the Determinants of Consumer Trust in Local Skincare Marketing: Overclaim, Perceived Product Quality, and Influencers - Alwi Alviansha; Khairina Tambunan; Nuri Aslami (Universitas Trunojoyo Madura, 2025)
The practice of overclaim in the marketing of local skincare products has intensified alongside increased social media promotion and influencer involvement, potentially undermining customer trust. This study analyzes the effects of overclaim, product quality perception, and the role of influencers on customer trust in the marketing of local skincare products. An associative quantitative design was employed in 2025 in Medan, North Sumatra, with a purposive sample of 100 users of local skincare products. Data were collected via a closed-ended questionnaire and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression with SPSS. Results indicate that overclaim exerts a significant negative effect on customer trust, while product quality perception and the role of influencers exert significant positive effects. Simultaneously, the three variables significantly explain variation in customer trust, with the role of influencers emerging as the most dominant predictor. The study’s novelty lies in integrating overclaim, product quality perception, and influencers into a single empirical model within the context of local skincare products affected by viral social media dynamics. Practical implications include the need for producers to reduce overclaim and strengthen empirical evidence of product quality in promotional activities, for regulators to tighten oversight of advertising claims, and for future research to examine mediation or moderation mechanisms such as influencer credibility and consumer characteristics.